2020
DOI: 10.3390/ijms21082734
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Dopaminergic Depletion Differently Affect Motor Thalamic Function

Abstract: The motor thalamus (MTh) plays a crucial role in the basal ganglia (BG)-cortical loop in motor information codification. Despite this, there is limited evidence of MTh functionality in normal and Parkinsonian conditions. To shed light on the functional properties of the MTh, we examined the effects of acute and chronic dopamine (DA) depletion on the neuronal firing of MTh neurons, cortical/MTh interplay and MTh extracellular concentrations of glutamate (GLU) and gamma-aminobutyric acid (GABA) in two states of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Our results show that the VAL/VM was the most dominant output-projection brain region of the rACC. Previous studies have shown that the VAL/VM belongs to the motor nucleus of the thalamus and is an internal brain area of the thalamus that encodes and integrates motor information ( Gaidica et al, 2018 ; Di Giovanni et al, 2020 ). The VAL/VM is not only involved in the execution of regulated movements but also in their planning ( Guo et al, 2017 ; Svoboda and Li, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the VAL/VM was the most dominant output-projection brain region of the rACC. Previous studies have shown that the VAL/VM belongs to the motor nucleus of the thalamus and is an internal brain area of the thalamus that encodes and integrates motor information ( Gaidica et al, 2018 ; Di Giovanni et al, 2020 ). The VAL/VM is not only involved in the execution of regulated movements but also in their planning ( Guo et al, 2017 ; Svoboda and Li, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased motor thalamic LTS bursting has been found in MPTP-treated primates ( Magnin et al, 2000 ; Devergnas et al, 2016 ) and in the dopamine deficient SPR-KO mouse model ( Kim et al, 2017 ). While assessment of VM bursting in awake rodents is yet lacking, a recent study shows increased bursting following 6-OHDA treatment recorded under urethane anesthesia ( Di Giovanni et al, 2020 ). Interestingly, in this study, an acute dopamine depletion led to a decrease in BGMT firing rate and increase in thalamic GABA transmission, whereas the chronic 6-OHDA depleted state resulted not in a firing rate change, but in increased bursting, supporting the notion of an intervening homeostatic mechanism as dopamine depletion persists.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpected alterations occurred (Grandi, Kaelin-Lang, et al, 2018) as the two states of DA depletion disclosed a decoupled activity between the MTh and the NRT, unmasking compensatory mechanisms and the putative role of NRT in the interplay between MTh and cortex. Furthermore, we recently observed that the acute TTX-driven DA depletion causes a reduction of MTh activity (Di Giovanni et al, 2020) parallel with the increment of firing activity of NRT (Figure 3); conversely following 6-OHDA, the changes of MTh activity were negligible, suggesting that the development of compensatory mechanisms was likely exerted by NRT in order to counteract the glutamate driven from the cortex.…”
Section: Disruption Oscillation and Synchronymentioning
confidence: 90%
“…Some remarks apply : The progressive induction of a dopaminergic neuron damage in 1–2 weeks allows an assessment of the probable compensatory mechanisms that go along with the dopaminergic deficits which we are not able to look at in PD patients, as they have already been well established. For instance, we demonstrated how the chronic DA depletion causes subtle changes in a crucial and often slightly investigated time point of the disease, that is, the MTh, considerably soon after the rapid interruption of the nigrostriatal pathway (DiGiovanni et al, 2020). Moreover, the effects on the neuronal oscillations, mainly in the β band range, that appear following the chronic denervation, suggest underling compensatory mechanisms which are even extra‐dopaminergic (Salvade et al, 2016).…”
Section: Final Commentsmentioning
confidence: 96%